2007
DOI: 10.1038/sj.onc.1210925
|View full text |Cite
|
Sign up to set email alerts
|

Ras isoform abundance and signalling in human cancer cell lines

Abstract: The ubiquitously expressed major Ras isoforms: H-, Kand N-Ras, are highly conserved, yet exhibit different biological outputs. We have compared the relative efficiencies with which epidermal or hepatocyte growth factor activates Ras isoforms and the requirement for specific isoforms in the activation of downstream pathways. We find that the relative coupling efficiencies to each Ras isoform are conserved between stimuli. Furthermore, in both cases, inhibition of receptor endocytosis led to reduced N-and H-Ras … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
106
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(120 citation statements)
references
References 32 publications
14
106
0
Order By: Relevance
“…1B) (14). This expression pattern is reminiscent of findings in other lymphoid leukemia cell lines (21) and peripheral T cells (20). Importantly, T cell costimulation via CD28, SLAM, or LFA-1 did not lead to significantly increased Ras-GTP formation as triggered by 5 mg/ml anti-CD3 (data not shown).…”
Section: Resultsmentioning
confidence: 53%
“…1B) (14). This expression pattern is reminiscent of findings in other lymphoid leukemia cell lines (21) and peripheral T cells (20). Importantly, T cell costimulation via CD28, SLAM, or LFA-1 did not lead to significantly increased Ras-GTP formation as triggered by 5 mg/ml anti-CD3 (data not shown).…”
Section: Resultsmentioning
confidence: 53%
“…Unfortunately, we were unable to efficiently suppress the expression of choline kinase in the hT/LT/Ras cells, which is likely due to poor transfection efficiency, as has been previously described (12.7 ± 3% using fluorescein-labeled nonsense siRNA; data not shown) (Telang et al, 2007). Unlike human bronchial epithelial cells, HeLa cervical carcinoma cells are easily transfected with high efficiency and express unmutated H-Ras, K-Ras and N-Ras, but maintain an activated Ras signaling pathway in the presence of serum (Omerovic et al, 2008). Initially, we examined the HeLa cells for choline kinase-a and choline kinase-b mRNA expression using reverse transcriptase-PCR and found that these cells expressed choline kinase a-1 and choline kinase-b, but not the choline kinase a-2 splice variant (35 cycles, data not shown).…”
Section: Resultsmentioning
confidence: 78%
“…[29] Interestingly, Ras association to endosomes exhibits isoform specificity: whereas N-and H-Ras establish stable interactions with the endosomal compartment, K-Ras does not. [11,30,31] These differences have been attributed to the modification of N-and H-Ras, but not of K-Ras, by ubiquitination. [31] At the PM, Ras proteins partition into microdomains referred to as ''nanoclusters.''…”
Section: Ras: An Actor On Many Stagesmentioning
confidence: 99%